ANALISIS KERASIONALAN PENGOBATAN PASIEN SKIZOFRENIA DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH KOTA X PADA JANUARI-JUNI 2015 - Nur’aini, Nur’aini; Rahayu, Mustika; Wijayanti, Rahayu (Jurnal Farmasi Indonesia, 2018)
Schizophrenia is a severe mental disorder with signs and symptoms which are diverse, both in degree and kind, and is often characterized with a chronic and recurrent trips. According to research in the various countries, the prevelance in the general population ranges from 1% - 3%. Antipsychotic drugs are considered as first-line therapy in schizophrenia. This study aimed to analyze the rationalization of the treatment of schizophrenia at pharmacy Plant of General Hospital X in January-June, 2015. Based on 8 T, namely the right diagnosis, precise indications of the disease, proper drug selection, right dosage, right route of administration, proper interval time of administration, appropriate duration of administration, wary of side effects on the population by the method of retrospective or data that are past which were then analyzed using Microsoft excel and are presented in tables and diagrams. The result of the data were taken from the installation of the patient medical record with the number 60. The results showed that of 60 patients 52 or 86.7% of them were not rational and 8 patients, or 13.3% rational. Proper diagnosis, appropriate treatment regimens, the exact time interval of drug administration, appropriate duration of administration have the same percentage that the level of rationalization of the 60 (100%) patients, the exact indication of the disease by 48 (80%) patients was not rational, and 12 (20 %) patients rational, be aware of drug side effects 50 (83.3%) patients who were not rational, and 10 (16.6%) patients who had a rational, appropriate doses of 58 (96.7%) patients and 2 (3,3%) irrational patients, the proper selection of drugs 14 (23.3%) patients that were not rational, and 46 (76.67%) rational